Measuring of exhaust gas emissions using absorption spectroscopy. (25th June 2007) - Hawe, Eamonn; Dooly, Gerard; Fitzpatrick, Colin; Chambers, Paul; Lewis, Elfed; Zhao, W.Z.; Sun, T.; Grattan, K.T.V.; Degner, M.; Ewald, H.; Lochmann, S.; Bramman, G.; et al.
This paper describes an optical fibre sensor for the detection of NOx (NO2 and NO) and CO2 in the exhaust system of a road vehicle. The measurement is based on a free path interaction zone which is interrogated using UV and NIR light guiding optical fibres and collimated lenses. Results are presented in the absorption spectra of the gases in the UV region for the NOx gases and NIR region for CO2. These demonstrate that using this method it is feasible to identify the individual CO2, NO and NO2 species as well as other gases in the exhaust system. Measurement of concentrations to the level of ten's parts per million (ppm) have been demonstrated for the NOxx gases.